THE RELATIONSHIP BETWEEN AVAILABILITY OF FACILITIES AND INFRASTRUCTURE WITH REFERRAL SYSTEM IN KONAWE DISTRICT PUBLIC HEALTH CENTER: REFERRAL SYSTEM - Yusni Dewi; La Ode Saafi; Yunita Amraini (STIKes Mandala Waluya Kendari, 2022)
Background: Increasing the ratio of referral systems and referral systems Online referral systems for outpatients are still a problem in the work area of the Konawe District Health Center, Southeast Sulawesi Province. This study aims to determine the relationship between the availability of facilities and infrastructure with the referral system for the Healthy Indonesia Card Guarantee in Konawe Regency. Methods: This type of research is a quantitative research with a cross sectional study design. The population is all public health centre that have health workers who have KIP and outpatients with Healthy Indonesia Cards in Konawe Regency who carry out examinations and outpatients as many as 87 people. The sample size in this study was 46 respondents, which were taken by simple random sampling. This research instrument uses a questionnaire that has been tested for validity and reliability. The data that has been collected, then analyzed using the chi square test and the test of the closeness of the relationship (phi coefficient). Results: The results of this study indicate that there is a strong relationship between the availability of facilities and infrastructure and the referral system for the Healthy Indonesia Card Guarantee in Konawe Regency, where X² count > X² count (31.843>3.841). Conclusion: Rehabilitative services have not been implemented properly at the public health center in Konawe Regency, because the facilities and infrastructure are not yet available to carry out these services. Therefore, it is necessary to procure facilities and infrastructure to support medical services at the public health center.